Optimalisasi Manajemen Program Pengabdian Masyarakat dalam Meningkatkan Keterampilan Sosial Anak Berkebutuhan Khusus Melalui Kegiatan Interaktif dan Edukatif - Nursafanah, Nafisah; Hidayah, Nur; Husna, Arinal; Ramadhani, Diva Nimas; Adinugraha, Hendri Hermawan (Welfare : Jurnal Pengabdian Masyarakat, 2025)
Law No 20 of 2003 affirms the right of every child, including children with special needs, to receive a proper education. However, limited facilities and a lack of interactive approaches in special schools (SLB) are still a challenge in developing the potential of children with disabilities. This service activity was carried out by the Novo Club Team in collaboration with FASA, which aims to increase creativity, social skills, and awareness of healthy living for SLB Negeri Slawi students. The implementation method uses a participatory approach through a series of coloring activities, hand washing education, and traditional games. This activity begins with an opening session, followed by the implementation of educational activities designed according to the characteristics of students with disabilities in SLB. The results of the service show that coloring activities are effective in stimulating creativity, hand washing education increases independence, and traditional games contribute to students' motor development and social interaction. This program is expected to become a model for inclusive interactive activities in other special schools.